HIPNOSIS LIMA JARI TERHADAP PENURUNAN CEMAS PADA PASIEN DIABETUS MELLITUS - Endah Wahyuningsih; Eni Hidayati (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
Anxiety is a feeling of subjectivity to a mental tension that arises as a common reaction of the inability to categorize problems or individuals feeling insecure (Hawari, 2011). Most of the Lapas residents experienced anxiety over their future when they were out of prison. Anxiety arises because of the perception of convicts that people have a poor view of the inmates so that it can affect its future (Sadock, 2010). The problems in the community are many people who oppose/have a bad view of the former convicts so that ex-convicts felt his life was unwanted in society. Negative views of the community will adversely affect the psychic condition of a former convict. These things can give a negative effect on inmates (Kartono, 2011). This research aims to be aware of the conception and anxiety of the existing youth in the prison (prison) Class 1 and Semarang. Using a descriptive correlation study, a cross sectional cut-off, the uptake with the total sampling method as much as 240 respondents. Data retrieval using questionnaires, analyses statistic using UNIVARIIC and bivariate analyses. The results of this study are the minimum age of study respondents 16 years and a maximum age of 23 years with a standard deviation of 1,802. A total of 211 respondents (87.9%) Muslim and 29 respondents (12.1%) Non-Islamic religion. Most of the respondents were 221 respondents (92.1%) Have a good self-economy, and 19 respondents (7.9) have less good self-economis. Category of respondents ' anxiety level as much as 193 respondents (80.4%) Has a low anxiety rate, and 47 respondents (19.6%) have high anxiety levels. A meaningful relationship between self-esteem against adolescent anxiety in the Class 1 prison of Kedungpane in Semarang.